The Influence of Social Media Marketing and Service Quality on Customer Satisfaction at Jastipwithluv - Lutfiyah Nazifah; Ismail Yusuf; Mira Nurfitriya (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study seeks to ascertain the impact of social media marketing and service quality on customer satisfaction. The research adopts a quantitative approach, employing both descriptive and verification methods. The population for this research comprised 350 customers who made purchases through Jastipwithluv in 2023. From this population, a sample size of 20% was selected, resulting in 70 respondents. Primary data was collected through questionnaires distributed to customers. Data analysis was conducted using various statistical tests, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination, all performed using the SPSS software. The findings indicate that social media marketing and service quality significantly and positively influence customer satisfaction at Jastipwithluv, accounting for 52.4% of the variation. This demonstrates that both social media marketing and service quality can effectively enhance customer satisfaction.